2017
DOI: 10.15171/jpd.2018.07
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic impact of cholecalciferol in patients with psychiatric disorders receiving olanzapine

Abstract: Introduction: Psychiatric disorders such as schizophrenia require appropriate treatment. Second-generation antipsychotics, including olanzapine, are administered as an appropriated treatment for these disorders. However, this drug has several complications, such as obesity and increased waist circumference which reduces the acceptance of the treatment. Objectives: The aim of this study was to investigate the effects of vitamin D3 therapy on waist circumference caused by olanzapine. Patients and Methods: In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The present study found that vitamin D supplementation during the exposure period to olanzapine suppressed the increase in the LDL cholesterol level, decrease in the HDL cholesterol level, increase in BMI, and increase in waist circumference. This is the first study to demonstrate the clinical significance of vitamin D in improving blood lipid profiles, since only one previous trial has shown that vitamin D helps in maintaining waist circumference in olanzapine-treated patients ( Kaviyani et al, 2017 ). Despite already being efficient in discovering the olanzapine-vitamin D interaction at the laboratory test level, the JMDC is still unable to precisely locate the onset time pattern of olanzapine-induced dyslipidemia due to the long data collection intervals.…”
Section: Discussionmentioning
confidence: 96%
“…The present study found that vitamin D supplementation during the exposure period to olanzapine suppressed the increase in the LDL cholesterol level, decrease in the HDL cholesterol level, increase in BMI, and increase in waist circumference. This is the first study to demonstrate the clinical significance of vitamin D in improving blood lipid profiles, since only one previous trial has shown that vitamin D helps in maintaining waist circumference in olanzapine-treated patients ( Kaviyani et al, 2017 ). Despite already being efficient in discovering the olanzapine-vitamin D interaction at the laboratory test level, the JMDC is still unable to precisely locate the onset time pattern of olanzapine-induced dyslipidemia due to the long data collection intervals.…”
Section: Discussionmentioning
confidence: 96%
“…Vitamin D supplementation in healthy overweight and obese women increased vitamin D blood concentrations and led to body fat mass reduction [39]. A study on female schizophrenic patients being treated with olanzapine found that administration of vitamin D was generally effective at reducing obesity [40], whereas, conversely, schizophrenic patients with vitamin D deficiency who were under treatment with clozapine did not undergo changes in their metabolic profile nor psychotic status [41].…”
Section: Discussionmentioning
confidence: 99%